Identifying Social Contexts Upon The Annual Homecoming Prohibition Due to The Covid-19 Outbreak - Kukuh Fadli Prasetyo (Udayana Journal of Law and Culture, 2021)
Despite its well-established value, the 1441 AH annual homecoming was prohibited by the Government of Indonesia to halt the COVID-19 outbreak. This paper aims to illustrate as well as analyse social factors that come up along with the implementation of the regulation. This research employs the so-called socio-legal research method. The intercourse between law and society has been discussed thoroughly. Later, the discussion builds a connection between law and society in which law initiates changes within society. Furthermore, as this regulation intends to adjust a well-established social value, this paper offers analysis from a perspective of sociology of law. There is a list of considerations to study. First, the legitimate lawmakers and the measurable benchmark are the main sociological strength of the law. Secondly, the absence of an integrated punishment and the ad-hoc basis of policy-making reduce the capacity to create social changes. Besides, other social factors ignored by the Government range from the recognition of this annual homecoming as social value to the ignorance of current social solidarity in Indonesia.